Prática de exergame em dupla x individual: efeitos na adesão ao exercício físico e na capacidade funcional de idosos - Silva Júnior, Jorge Luiz Andrade da (2019)
In the process of human ageing there is a decline in functional capacity, the skills needed for the individual to perform the tasks of daily living independently. Among the strategies adopted to reduce the effects of this loss there is the regular practice of physical exercise, which has a low adherence by the elderly population. The lack of motivation is one of the most pointed aspects. In this perspective, current interactive technological innovations have been used as motivational resources, such as exergames. Such games act as a virtual mirror, capturing the player's body movements and transmitting them virtually on a TV, as well as providing performance feedback in performing the exercise. The general goal of this research was to evaluate the effects of the practice of exergame in pairs on the adhrence to the physical exercise and functional capacity of the elderly. The specific goals were: i) to compare the adherence of the elderly to the physical exercise pre and post intervention with the exame practice individually and in pairs; ii) to evaluate the functional capacity of the elderly before and after the intervention with the exame practice individually and in pairs; iii) to attend in the design of exergame. The research was organized in seven stages: game design, game design, pre-intervention, intervention, postintervention, information analysis and game making. The user tests were conducted through a non-randomized clinical trial, which involved elderly people aged 20-60 years and over. The participants, CAMTI’s members (Senior Caixeral Campestre) belonging to the Caixeral Campestre Club of Passo Fundo / RS, were divided into two groups: Group in Pairs (GP) and Group in Individual (GI). The interventions provided 21 sessions twice a week in total. The exergame used for intervention was a bowling game, Virtual Bowling, developed with the Xbox Kinect platform. The results demonstrate that both groups presented statistically significant results for functional capacity. However, in the comparison between the groups there was no significant difference. In adhering to physical exercise, both groups presented interest in playing together, therefore the social presence in the game helps to solve their problems. These results prove that the effects of exergame are effective in improving functional capacity and adherence to physical exercise of the elderly. The Virtual Bowling exergame, specific goal iii, was developed in partnership with the Computer Science course of the University of Passo Fundo. All results will be present in the form of a scientific production that will be submitted later in a academic periodic in the ageing area.